A One Health approach to assessing occupational exposure to antimicrobial resistance in Thailand: The FarmResist project - Duangdao Sudatip (2022)
This Southeast Asia-Europe research project will use a One Health approach to identify the major parameters responsible for the presence of animal-associated antimicrobial resistant bacteria in animal production facilities in Thailand and the risk of their transmission from animals to humans. We will focus on traditional, small, extensive pig and poultry farms where information on antibiotic use is scarce and animals live in close contact with humans. This cross-sectional study will be based on the epidemiological analysis of the antimicrobial resistance (AMR) present in fecal samples from animals and humans. Extended spectrum beta-lactamase producing Enterobacteriaceae (ESBL-E) and Enterobacteriaceae resistant to colistin will be actively searched in the feces of farm animals (pigs and poultry), small wild rodents and farmers. Phenotypic (selective plating) and genotypic (multilocus seuquence typing and sequencing) methods will be used for the detection of AMR, the identification of antibiotic resistance genes (ARGs) and the characterization of strains carrying resistance genes. Questionnaires will be administered to investigate the effects of antibiotic use, farm characteristics and biosecurity measures on the occurrence of AMR in animals. Subsequently, the fecal carriage of AMR and ARGs in farmers will be compared to a control population with no occupational contacts with animals, thus enabling an estimation of the risk of transmission of AMR/ARGs from animals to farmers.